ЗАВИСИМОСТЬ ВОЗМУЩЕНИЙ ЭЛЕКТРИЧЕСКОГО ПОЛЯ В ДИЭЛЕКТРИКЕ ОТ ДИСПЕРСНОСТИ БЛИЗКО РАСПОЛОЖЕННЫХ ВОДНЫХ МИКРОВКЛЮЧЕНИЙ - Щерба , М.А.; Розискулов , С.С.; Васильева , О.В. (Інститут електродинаміки НАН України, Київ, 2014)
The regularities of electric field disturbances in dielectric, depending on the dispersity of its closely spaced water micro-inclusions were defined. It was revealed that fragmentation of micro-inclusions (i.e. when its number increases at invariable its summarized volume) increases the tensed volume of dielectric. The configuration change both closely spaced inclusions aggregate ("cloud") and each inclusion individually can also result in increase the tensed volume. In particular the increase of dielectric tensed volume occurs when water microinclusions are stretched and distances between them are decreased. The greatest disturbance of the electric field occurs when stretched inclusions coalesce in one conducting structure along the field. Thus, it is shown that the appearance of small water inclusions aggregate for solid dielectric is more dangerous in the view of its structure degradation than a few large inclusions. References 5, figures 3.